Transplant Associated Thrombotic Microangiopathy in Individuals with Fanconi Anemia - Myers, Kasiani C.; Jodele, Sonata; Nelson, Adam S.; Goodridge, Erica; Mehta, Parinda A; Mueller, Robin; Dandoy, Christopher E.; Lane, Adam; El-Bietar, Javier A.; Davies, Stella M (Blood, 2016)
Objective: Transplant-associated thrombotic microangiopathy (TA-TMA) is an increasingly recognized complication of hematopoietic stem cell transplantation (HSCT) due to vascular endothelial injury. TA-TMA most commonly affects the kidneys resulting in proteinuria, hypertension and often progresses to multi-organ failure in severe cases. We previously identified in our institutional prospective study of TA-TMA a higher incidence of TA-TMA in Fanconi anemia (FA) individuals. We hypothesized that exposure to cyclosporine (CSA), which has been implicated in TA-TMA, may have led to this increase. The goal of our current study was to examine the TA-TMA incidence in FA individuals undergoing HSCT with CSA exposure at our institution and its impact on transplant related morbidity and organ function. Methods: We performed a retrospective chart review in all patients with FA undergoing first unrelated donor T-depleted HSCT (2010-2016) using a busulfan, fludarabine, cyclophosphamide and ATG preparative regimen to identify the incidence of transplant-associated TMA and clinical outcomes. Subjects were stratified by cyclosporine use. Results: Forty-two patients underwent unrelated donor t-depleted HSCT using busulfan, fludarabine, cyclophosphamide and ATG during the study period. Additional GVHD prophylaxis with cyclosporine (CSA) was used in the first 29 subjects while subsequent subjects received no additional prophylaxis (n= 13). Incidence of TA-TMA in the CSA and Non-CSA groups was 66% (n=19/29) and 54% (n=7/13) respectively (p=0.51) and was increased from the overall institutional TA-TMA incidence of 34% (p=0.0011). Risk factors for severe TA-TMA were increased in the CSA-group with nephrotic range proteinuria in 53% compared with 14% of the non-CSA group in tested patients and increased complement activation by sC5b-9 levels 100% vs 20%. Median duration of active TA-TMA was longer in the CSA-group at 85 days compared with 41 in the non-CSA group. Complications of TA-TMA including hypertension, kidney injury, dialysis, pericardial effusion and pulmonary hypertension were all increased in the CSA group compared to the non-CSA group. Conclusion: Incidence of TA-TMA after HSCT is increased in FA compared to other HSCT recipients. Individuals receiving cyclosporine for GVHD prophylaxis had more severe TA-TMA than those who did not receive it, affecting transplant related morbidity and long-term renal function. Increased incidence of TA-TMA in individuals with FA may point to novel mechanisms of vascular endothelial injury. Better understanding of these mechanisms may allow for improved transplant risk stratification or new therapeutic approaches in solid tumor therapy. Davies:Novartis: Honoraria.